Minix over Linux: A User-Space Multiserver Operating System - Pessolani, Pablo; Jara, Oscar (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2011)
Minix is an open-source multiserver operating system designed to be highly reliable, flexible, and secure. The kernel is small and is the only piece of software that runs in privileged-mode, on the other hand user processes, specialized servers and device drivers run as isolated processes in user-mode. System Calls use Interprocess Communications primitives to send messages requesting services from the servers, and to wait for response messages. The aim of the project described in this article is a user-space multiserver operating system (a modified Minix version) running on top of a middleware-based virtual machine with simulated hardware constructed from services provided by a host operating system (Linux).